Eye Movement Measurement in Diagnostic Assessment of Disorders of Consciousness - Ting, Windsor Kwan-Chun; Perez Velazquez, Jose Luis; Cusimano, Michael D. (Frontiers in Neurology, 2014)
We review the literature to appraise the evidence supporting or disputing the use of eye movement measurement in disorders of consciousness (DOC) with low levels of arousal or awareness, such as minimally conscious state (MCS), vegetative state (VS), and coma for diagnostic and prognostic purposes. We will focus on the effectiveness of each technique in the diagnostic classification of these patients, and the gradual trend in research from manual to computerized tracking methods. New tools have become available at clinicians’ disposal to assess eye movements with high spatial and temporal fidelity. The close relationship between eye movement generation and organic dysfunction in the brain allows these tools to be applied to the assessment of severe DOC as a unique supplementary toolset. We posit that eye tracking can improve clinical diagnostic precision for DOC, a key component of assessment that often dictates the course of clinical care in DOC patients. We see the emergence of long term eye tracking studies with seamless integration of technology in the future, to improve the performance of clinical assessment in disorders of consciousness.